Long-Term High-Temperature Stress Impacts on Embryo and Seed Development in Brassica napus - Mácová, Kateřina; Prabhullachandran, Unnikannan; Štefková, Marie; Spyroglou, Ioannis; Pěnčík, Aleš; Endlová, Lenka; Novák, Ondřej; Robert, Hélène S. (Frontiers in Plant Science, 2022)
Brassica napus (rapeseed) is the second most important oilseed crop worldwide. Global rise in average ambient temperature and extreme weather severely impact rapeseed seed yield. However, fewer research explained the phenotype changes caused by moderate-to-high temperatures in rapeseed. To investigate these events, we determined the long-term response of three spring cultivars to different temperature regimes (21/18 °C, 28/18 °C, and 34/18 °C) mimicking natural temperature variations. The analysis focused on the plant appearance, seed yield, quality and viability, and embryo development. Our microscopic observations suggest that embryonic development is accelerated and defective in high temperatures. Reduced viable seed yield at warm ambient temperature is due to a reduced fertilization rate, increased abortion rate, defective embryonic development, and pre-harvest sprouting. Reduced auxin levels in young seeds and low ABA and auxin levels in mature seeds may cause embryo pattern defects and reduced seed dormancy, respectively. Glucosinolates and oil composition measurements suggest reduced seed quality. These identified cues help understand seed thermomorphogenesis and pave the way to developing thermoresilient rapeseed.